PERAN UNITED NATIONS ENVIRONMENT PROGRAMME (UNEP) DALAM MENANGANI ILLEGAL LOGGING DI INDONESIA TAHUN 2014-2018 - Fitrya "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to explain the general picture of Illegal Logging in Indonesia and the role of the United Nations Environment Programme (UNEP) and Indonesian policies in dealing with illegal logging in Indonesia. The research method used was qualitative research. This research was focused on discussing the role of the United Nations Environment Programme (UNEP) and Indonesian policies in dealing with illegal logging. Then, the researcher was gave time limits for the phenomena or problems to be examined, namely in 2014-2018.                This research used the pluralism theory. The research also used International Organization analysis. The study concluded that UNEP provides effective programs in solving illegal logging problems that occur in Indonesia. These programs are CDM, REDD +, and the Great Apes Survival Partnership (GRASP). These programs do not directly give solution for the problem of illegal logging in Indonesia, but it was very effective in solving the problem of illegal logging generally. Because with the program above, indirectly Indonesia’s forests will be increasingly tightly guarded by the Indonesian government and increasingly narrow the perpetrators of illegal logging in Indonesia. Keywords: Role, UNEP Program, Illegal Logging